IMPROVING ORGANIZATIONAL PERFORMANCE (OP) THROUGH SUPPLY CHAIN MANAGEMENT PRACTICES (SCMP) AND STRATEGIC INFORMATION SYSTEM (SIS) WITH COMPETITIVE ADVANTAGE (CA) MEDIATION IN MICRO SMALL AND MEDIUM ENTERPRISES (MSMEs) IN SOLO RAYA - Cahyaningrum, Bambang Nur; Untoro, Wisnu; Setiawan, Ahmad Ikhwan; Wahyudi, Lilik (CENTRAL ASIA AND THE CAUCASUS, 2022)
The purpose of this study was to find out how to improve organizational performance (OP) by implementing supply chain management practices (SCMP) and strategic information systems (SIS), in micro small and medium enterprises (MSMEs). The population and sample used are MSME actors in the Solo Raya area, which include: Surakarta City, Sragen Regency, Boyolali Regency, Klaten Regency, Sukoharjo Regency, Karanganyar Regency and Wonogiri Regency. The collection of respondents who are used as samples using google forms, which are distributed online. The sample criteria used are MSMEs, that have used or interacted with information technology or the internet. Data entered and can be used as many as 184 respondents. The research approach used is a structural equation model (SEM), the processing use the analysis moment of structural (AMOS) application program. Data processing carried out includes: selecting data that meets the criteria, then: validity test, reliability test, outlier evaluation, data normality test, goodness-of-fit model, and path coefficient analysis, which is continued by discussion, conclusions are made, the implications are explained, the limitations are described, and suggestions are made for further researchers as well as for MSMEs. The results of this study are: Supply chain management practices and strategic information systems, do not have a direct impact on organizational performance. However, strategic information systems can have a positive impact on competitive advantage and organizational performance levels. Competitive advantage (CA) can improve organizational performance. Furthermore, competitive advantage was found to fully mediate, on the influence of strategic information systems on organizational performance. However, competitive advantage is not able to mediate the effect of supply chain management practices on organizational performance. To improve the organizational performance of MSMEs, especially micro, not only by implementing a good strategic information system, but also needs to be supported by increasing competitive advantage.